Sistem Scheduling Pelaporan Data Akademik di UIN Sunan Kalijaga ke Pangkalan Data Pendidikan Tinggi (PDDikti) dengan Menggunakan Fitur Cron Job di Linux - Adi Wirawan (JISKA (Jurnal Informatika Sunan Kalijaga), 2020)
Data reporting from higher education to the Higher Education Data Centre (PDDikti) is a form of reporting that must be sent to The Indonesian Ministry of Research, Technology and Higher Education (Ristekdikti). This reporting includes aspects of students, academic transactions, and some other data, which usually has a time limit for each academic year. UIN Sunan Kalijaga like other higher eductions, reports a lot of data to PDDikti with a limited time, which sometimes makes reporting officers need to do overtime to report existing data. This study aims to create an application that can schedule data reporting times to the PDDikti feeder application, to reduce overtime that needs to be done by the operator. The application is created using the cron job feature owned by Linux to run reporting commands.